THE FULFILLMENT OF ECONOMIC AND MORAL RIGHTS OF INDIGENOUS PEOPLES ON TRADITIONAL KNOWLEDGE AND TRADITIONAL CULTURAL EXPRESSIONS THROUGH INDONESIA'S TPR's SYSTEM - Dwi Martini (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
Economy and moral rights are the part of basic human rights entitled to the proprietor of theintellectual property that must be full filed by the state, to meet the requirements of Constitution.Similar treatment must be provided by the state to economic and moral rights of indigenouspeoples on their own Intellectual Property, in the form of Traditional Knowledge and TraditionalCultural expressions as described in Article 18 b of the Constitution of 1945 “The state recognizesand respects the customary law community units including their traditional rights as long as itexists and in accordance to society development and principles of Unitary State of The Republicof Indonesia, as stated by the Law.”. Fulfilment of these rights through modern TRIPs-WTOIPRs regime brings about legal problems, considering their different character, where individualand commercial character of modern IPRs contradicts the communal and non-commercialcharacter of Traditional Knowledge and Traditional Cultural Expression. On the other hand,to get modern IPRs protection, Traditional Knowledge and Traditional Cultural Expressionmust meet particular conditions such as originality/ novelty, inventive step and applicable toindustry which indeed unable to fill due to its anonymous inventor, developed and bequeathedfrom generation to generation and is not intended specifically for industrial/commercial purpose.Keywords: Rights, Indigenous Peoples